Critical Latin American pedagogy and its transformative element in the Spontaneous Theater: A work experience on the issue of labor discrimination - Rodríguez Víquez, Francisco Javier (2020)
In this article there will be a dialogue between a group experience facilitatedby the methodology of the Spontaneous Theater (T.E.) in its Workshop-functionmodality and Paulo Freire's postulates on Latin American critical pedagogiesin the context of a hardware company. This work experience wascarried out to problematize the concepts of discrimination and harassmentin the framework of the implementation of the Labor Procedural Reform(2018, Costa Rica). Throughout this, findings are presented that have coherencebetween the praxis of T.E. and the theories of Latin American criticalpedagogies. Epistemological and ontological similarities of working withT.E. with a critical Latin American vision on the importance of the role ofpeople in a group in the joint construction of social transformations regardinga particular theme are shown.